The taming of the samurai : - Ikegami, Eiko (Harvard University Press, 1995)
This book has already been widely praised by prominent American political scientists and historians for answering how the Japanese achieved modernity without traveling the route taken by Western countries. At once a remarkable historical study of the samurai warrior class from its ancient origins to its transformation under the Tokugawa regime and a comparative study that makes Japan available for analysis alongside other great instances of state formation...Beautifully written. It will undoubtedly become standard reading in universities around the world.